2017
DOI: 10.4236/me.2017.88073
|View full text |Cite
|
Sign up to set email alerts
|

Can Overconfident Executives Restrain Overinvestment?

Abstract: This paper uses the data of the public company from 2013 to 2015 to explore the relationship between executives' overconfidence and overinvestment when the company's financing ability is different. Unlike previous studies, the result of this study shows that overconfidence may curb overinvestment when the company's financing capacity is poor. It is when the financing capacity is strong that overconfidence will exacerbate overinvestment. A lot of studies show that overconfident executives increase overinvestmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Using data from public companies between 2013 and 2015, Liu [39] examined the relationship between overconfidence of executives and overinvestment, as well as the ways in which the relationship changes depending on the financing ability of the company. The outcomes suggested that, when the financing ability of the company is low, overconfidence may limit overinvestment.…”
Section: Prior Research On Investment Efficiencymentioning
confidence: 99%
“…Using data from public companies between 2013 and 2015, Liu [39] examined the relationship between overconfidence of executives and overinvestment, as well as the ways in which the relationship changes depending on the financing ability of the company. The outcomes suggested that, when the financing ability of the company is low, overconfidence may limit overinvestment.…”
Section: Prior Research On Investment Efficiencymentioning
confidence: 99%
“…Recent studies on global overinvestment have primarily been conducted in the United States and China, and they are contentious in a variety of ways. Typically, studies in China focus on assessing overinvestment behavior and the factors that explain this overinvestment behavior [4][5][6][7] . Overinvestment is closely related to the use of corporate debt.…”
Section: Introductionmentioning
confidence: 99%